2017
DOI: 10.1002/ijgo.12286
|View full text |Cite
|
Sign up to set email alerts
|

Risk of appendiceal endometriosis among women with deep‐infiltrating endometriosis

Abstract: Women with DE have increased risk of AppE. Coincidental appendectomy should form part of complete endometriosis excision for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 26 publications
10
34
0
Order By: Relevance
“…Among all these patients, the presence of appendiceal neoplasia was detected in one patient, leading to a frequency of appendiceal neoplasia of 1 in 12 (8.3%) among all our appendectomies and 1 in 124 (0.8%) of all surgeries for DIE with intestinal resection. The incidence of appendectomies in our series is comparable with that in other series [4,12], which reinforces the importance of a complete evaluation of the peritoneal cavity during laparoscopy in patients with DIE. In addition, it is essential to map the endometriosis lesions during the preoperative evaluation to facilitate surgical planning and ensure a complete evaluation of the intestine during laparoscopy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among all these patients, the presence of appendiceal neoplasia was detected in one patient, leading to a frequency of appendiceal neoplasia of 1 in 12 (8.3%) among all our appendectomies and 1 in 124 (0.8%) of all surgeries for DIE with intestinal resection. The incidence of appendectomies in our series is comparable with that in other series [4,12], which reinforces the importance of a complete evaluation of the peritoneal cavity during laparoscopy in patients with DIE. In addition, it is essential to map the endometriosis lesions during the preoperative evaluation to facilitate surgical planning and ensure a complete evaluation of the intestine during laparoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…Surgery is indicated in patients with pelvic pain who do not respond to medical therapy and/or in patients with ileal involvement, owing to the risk of intestinal obstruction, and in those with appendiceal involvement, owing to the higher risk of neoplasia in these cases [2,4]. Previous studies have suggested that appendiceal endometriosis is not a rare entity and occurs in up to 2.8% of patients with endometriosis [5] and up to 13.2% of patients with DIE [4]. The percentage is higher in patients with more severe disease or in those with lesions at multiple sites [4].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the patients evaluated, nearly 50% have deep involvement by endometriosis, while 32% showed appendiceal involvement. 16 Although these patients were asymptomatic, the level of infiltration was indicative for surgical intervention. 16 It has been suggested that prophylactic concurrent appendectomy be performed as part of complete endometriosis excision.…”
Section: Discussionmentioning
confidence: 93%
“…16 Although these patients were asymptomatic, the level of infiltration was indicative for surgical intervention. 16 It has been suggested that prophylactic concurrent appendectomy be performed as part of complete endometriosis excision. 16 Unusually, other intra-abdominal pathology can be mimicked by pain from appendiceal endometriosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation